Postcolonial Hangups in Southeast Asian Cinema : Poetics of Space, Sound, and Stability - Sim, Gerald (Critical Asian cinemas., 2020)
Postcolonial Hangups in Southeast Asian Cinema explores a geopolitically situated set of cultures negotiating unique relationships to colonial history. These particular Singaporean, Malaysian, and Indonesian identities are discussed through a variety of commercial films, art cinema, and experimental work. It discovers instances of postcoloniality that manifest stylistically through Singapore's preoccupations with space, the importance of sound to Malay culture, and the Indonesian investment in genre.